Anti-Quorum Sensing Effects of Some Medicinal and Aromatic Plant Extracts on Xanthomonas axonopodis pv. Phaseoli - Tibebu Belete; Kubilay Kurtulus Bastas (Turkish Journal of Agriculture: Food Science and Technology)
Xanthomonas axonopodis pv. phaseoli (Xap) is known as one of the most important seed-borne destructive pathogens on beans worldwide. Nowadays, Xap is considered to acquire resistance to antibiotics and synthetic bactericides which concerns the scientific world for its future management. This has made the use of plant extracts, the best alternative in the control of plant disease pathogens by inhibiting the quorum sensing (QS) mediated virulence factors. This research was designed to investigate the antibacterial activities and the anti-QS effects of the 14 different aromatic and medicinal plants against QS-mediated virulence factors of Xap. The results revealed that Syzgium aromaticum showed the largest inhibition zone diameter and strongest antimicrobial (antibacterial) effect among the 14 plant extracts followed by Thymus vulgaris and Coriandrum sativum. Similarly, the lowest swarming, swimming, and twitching motility values were measured from the Syzgium aromaticum application followed by Coriandrum sativum, Thymus vulgaris, Brassica nigra, Lepidium sativum, and Ruta chalepenis. These results indicated that S. aromaticum, C. sativum, T. vulgaris, B. nigra, L. sativum, and R. chalepenis will be a potential candidates as anti-quorum sensing agents in preventing common bacterial disease of beans caused by Xap. Compounds derived from aromatic and medicinal plants have demonstrated successful control of diseases in crops and the use of these substances provides a valuable tool to the growers around the world for diseases management in organic production.